Gaya Bahasa pada Lirik Lagu "Jakarta Hari Ini" Karya For Revenge dan Stereo Wall - Ibrahim Habib Anshari (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
The purpose of making this article is to find out what the lyrics of the title "Jakarta Today" mean. And also to find out what are the styles of language or figure of speech contained in the lyrics of the song "Jakarta Today" as well as some of our goals, especially in this song, especially for people who are in a position between advancing or retreating from a choice and also about heartbreak. what he wrote is an illustration of a different level of heartbreak because it tells the relationship between humans. Jakarta is an interesting setting to take up because it brings a deep impression on the vocalist's life. Jakarta teaches many things to be human The theory we use according to some well-known experts. The method we use in this journal is by listening to the song and reading the lyrics to the song. The result of our analysis is that every lyric of the song “Jakarta Hari Ini” contains many meanings that we must learn. Our recommendation to establish a relationship should lower each other's ego so that they complement each other's shortcomings.